2016
DOI: 10.21608/adjalexu.2016.59261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Different Bleaching Concentrations on Microleakage and Microhardness of Tooth-Colored Restorations (An in Vitro Study)

Abstract: INTRODUCTION: Bleaching may exert some negative effects on existing resin restorations. OBJECTIVES: To evaluate the effect of bleaching with 14% and 40% hydrogen peroxide on microleakage and microhardness of different tooth-colored restorations. MATERIALS AND METHODS: MICROLEAKAGE TEST: Class V cavities were prepared on labial surfaces of 60 extracted human upper central incisor teeth. The teeth were divided into 2 groups: Group I: restored with FiltekZ350XT composite, Group II: restored with Fuji II LC resin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Polydorou et al [13] also found that bleaching agent has no tendency to substantially reduce the composite materials' microhardness, and so it appears that the replacement of composite restorations is not required following bleaching treatment. Similar findings were proposed in the study of Ahmed et al [19] who evaluated the effectiveness of bleaching with hydrogen peroxide on the microhardness and microleakage in the restoration of tooths. Cavities of class V were prepared focusing on the labial surfaces upon 60 extracted human upper central incisor teeth.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Polydorou et al [13] also found that bleaching agent has no tendency to substantially reduce the composite materials' microhardness, and so it appears that the replacement of composite restorations is not required following bleaching treatment. Similar findings were proposed in the study of Ahmed et al [19] who evaluated the effectiveness of bleaching with hydrogen peroxide on the microhardness and microleakage in the restoration of tooths. Cavities of class V were prepared focusing on the labial surfaces upon 60 extracted human upper central incisor teeth.…”
Section: Discussionsupporting
confidence: 86%
“…The teeth were immersed in die before analysis. Findings of the study indicated that bleaching had no effect on microleakage of Filtek Z350XT composite along with the compositions of Fuji II LC RMGI restorations while the microhardness of these restorations were also affected [19].…”
Section: Discussionmentioning
confidence: 90%